Subjective Well-being, Income, and Ethnicity in Slovakia - Tomáš Želinský (Global Labor Organization (GLO), 2021)
This paper utilizes two measures of subjective well-being to test a hypothesis that a marginal increase in subjective well-being associated with a marginal increase in income is larger for poorer than for richer populations. This hypothesis is examined in the setting of Slovak Roma, who are poor in comparison to the non-Roma population. The results suggest that the correlation between income and satisfaction is greater for the lower-income group (the Roma) than for the higher-income group (majority population). Further, the correlation between income and emotional well-being does not differ between the two groups.
Keywords: I31; J15; 330; Satisfaction; Emotional well-being; Roma; Income; Poverty